Financial Variables Effect on the Initial Return And the company´s Performance 2 Years After IPO Companies Manufacturing in Indonesia Stock Exchange - Susilowati, Wahyunita; one, Dr. Masodah (Accounting, 2009)
The development of the company in an effort to anticipate the increasingly sharp competition in an increasingly global marketplace it is today will always be done either by companies large and small companies. The effort is a problem for companies, because it involves the fulfillment of the necessary funds. In the process, if the company becomes greater will increasingly need additional capital. Based on statistical analysis as described above, then the conclusions of this study can provide a sample of 17 manufacturing companies that do an IPO on the Indonesia Stock Exchange during the period 2001 to 2005 are as follows: No financial variables that influence initial returns. There are changes in the company´s performance 2 years after the IPO, namely return on assets and profit margins. Meanwhile Current Debt to asset ratio and the ratio changed in the 2 years after the IPO even though the change is temporary and inconsistent. Keywoeds : Financial Variables, initial Return, the company´s Performance, IPO, Companies Manufacturin